Effectiveness and safety of betahistine in treatment naive acute peripheral vertigo patients - Pereira, Carlton (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objective of the study was to assess the effectiveness and safety of oral betahistine in treatment naïve patients with acute peripheral vertigo, administered over 21 days. Methods: Treatment naïve patients with confirmed peripheral vertigo, based on clinical diagnosis, were enrolled in this open-label, single-arm, interventional study. Patients received 48 mg betahistine (16 mg, TDS) for 21 days, and were followed up on day 1, 3, 7 and 21. Safety and effectiveness were assessed based on clinical response (scale for vestibular vertigo severity level and clinical response evaluation (SVVSLCRE)); frequency and severity of peripheral vertigo (videonystagmography (VNG)); dizziness handicap inventory (DHI). Results: Overall, 53 (70.67%) out of 75 enrolled patients completed 21 days of treatment and were included in the study. No significant improvement in SVVSLCRE score was noted from baseline to day 1 (p=0.0572), but significant reduction was seen from day 3 onwards and continued till day 21 (p<0.0001). Level wise severity analysis showed that patients with ‘moderate to severe’ category at baseline reported ‘mild’ severity on day 7. A significant reduction in mean change of DHI scale was observed from baseline to day 3, day 7 and day 21 (p<0.0001). No major therapy related serious adverse events were reported. Headache (4.0%) and nausea (2.6%) were the commonly reported adverse events, which were mild in nature. Conclusions: Findings suggest that 48 mg betahistine (16 mg, TID) therapy is effective in treatment naive patients with acute peripheral vertigo. Reduction in vertigo symptoms score was significant from day 3 to day 21. Betahistine was found to be safe and easily tolerated in these patients.